Fundamental of Entrepreneurship ENT300 : De' Crepe Enterprise / Hapisah Jumaat ... [et al.] - Jumaat, Hapisah; Sarif, Fatimah; Latip, Nur Atikah; Madi, Nazatul Ikma; Barri, Nazinordina; Ismail, Ira Sharmilla (Universiti Teknologi Mara Cawangan Sarawak, 2016)
The name of our company is De'crepe Enterprise whereby the business has been decided the fom of six partnerships. Our main business activity is to provide the best and delicious of crepe. This business plan gives us the opportunity to assess on business industry in the future. We decided to fom a pattnership business which in desert industry.All shareholders had agreed as stated in the agreement letter that mentioned about the capital, contribution, loss and profit of the business. Every partner in the business are enftled and encouraged to participate in all business. We choose this business because it shows that crepe is a zewdesett and not all the people Ismowsabout the crepe.